Context matters: Longitudinal associations between marital relationships and sibling relationships in Black families. Issue 3 (5th March 2022) - Skinner, Olivenne D.; McHale, Susan M.
Abstract: Objective and Background: Sibling relationship qualities have been linked to parents' marital dynamics, but we know little about the contextual conditions underlying these linkages. We examined longitudinal associations between parents' reports of their marital satisfaction and conflict and siblings' reports of warmth and conflict and tested whether these associations varied by family economic strain, neighborhood economic disadvantage, and parent and youth gender. Method: Data were collected in three annual home interviews with mothers and fathers and two adolescent siblings from 185 Black families. Results: Results from multilevel models showed that associations between mothers' and fathers' marital and youth's sibling relationship varied according to neighborhood socioeconomic disadvantage, family economic strain, and youth gender. For example, consistent with a spillover model, on occasions when parents reported more marital conflict than usual, youth reported less sibling positivity, but only when parents also experienced less economic strain than usual. Supporting a compensation hypothesis, on occasions when parents reported more marital conflict than usual, boys reported more sibling positivity. Conclusions: Results provide new insights into family systems processes in an understudied group, including the role of contextual factors and youth gender in shaping those processes. Implications: Researchers and practitioners should consider multiple family relationship dynamics and the larger family contexts in which these relationships take place to better understand youth relational adjustment.